Physical activity maintenance and metabolic risk in adolescents - Silva, Danilo R.; Werneck, André O.; Collings, Paul J.; Fernandes, Rômulo A. [UNESP]; Barbosa, Décio S.; Ronque, Enio R.V.; Sardinha, Luís B.; Cyrino, Edilson S. (Oxford University Press (OUP), 2018)
Aim Examine the association between child and adolescent physical activity maintenance categories and metabolic profile in adolescence. Methods This cross-sectional study was conducted with 1152 adolescents (57.4% female) aged 10-16 years from Londrina, Brazil. Physical activity was self-reported in childhood (7-10 years old, retrospective data) and adolescence through questionnaires. Cardiorespiratory fitness (20m shuttle-run test), body fat (skinfolds), waist circumference, blood pressure (automatic instrument) and blood variables (fasting glucose, HDL-cholesterol and triglycerides) were measured at adolescence. Results Frequency of physical activity in childhood and adolescence was 50.3 and 17.2%, respectively, and only 25.7% of boys and 10.9% of girls were active at both ages. Adolescents who were physically active in childhood alone were less likely [OR = 0.71 (95% CI: 0.52-0.97)] to present low cardiorespiratory fitness in adolescence compared to those who were non-active in childhood. Regardless of controlled, actives in childhood and adolescence were less likely to present low cardiorespiratory fitness [OR = 0.50 (95% CI: 0.34-0.73)], high blood pressure [OR = 0.52 (95% CI: 0.32-0.85)] and high metabolic risk score [OR = 0.44 (95% CI: 0.22-0.90)] compared to the non-actives at both ages. Conclusions Actives through childhood to adolescence are less likely to present low cardiorespiratory fitness, high blood pressure and high metabolic risk.
Keywords: Adolescent; Metabolic diseases; Physical activity